2022
DOI: 10.1177/00405175221139319
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the contacting area of spacer fabric under spherical compression

Abstract: Spacer fabrics have been developed into a variety of special textile mattress products due to their outstanding pressure distribution performance. It may be that the contacting area of spacer fabrics can be expanded under spherical compression. The total compression force and distance curve is currently used to test the compression of spacer fabrics; however, there are few detailed reports about expanding the contacting area under the spherical intender. Therefore, this paper developed a test method for the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…It has also found that compression resistance under spherical indentation increases with increasing the spherical indenter radius and decreases with increasing the fabric thickness. [20][21][22] Several finite element (FE) models have been developed by simplifying the outer layers of spacer fabrics into uniform hexagonal mesh structures 23 or homogeneous plates 24 and the spacer monofilaments as discrete slender elastic rods with an identical spatial form. 23,24 However, the monofilament architecture of spacer fabrics is intermeshed and continuous.…”
Section: Introductionmentioning
confidence: 99%
“…It has also found that compression resistance under spherical indentation increases with increasing the spherical indenter radius and decreases with increasing the fabric thickness. [20][21][22] Several finite element (FE) models have been developed by simplifying the outer layers of spacer fabrics into uniform hexagonal mesh structures 23 or homogeneous plates 24 and the spacer monofilaments as discrete slender elastic rods with an identical spatial form. 23,24 However, the monofilament architecture of spacer fabrics is intermeshed and continuous.…”
Section: Introductionmentioning
confidence: 99%